The Dual Alliance Under the Perspective of the Theory of Alliance Dilemma: A Study Centered on Macedonian Reforms (1903-1908) - Gao Jianzhi («Մռավ» հրատ․)
The Dual Alliance was an important achievement of Germany’s proactive diplomacy, which eliminated the hidden security risk of Austria-Hungary’s fall to the hostile countries, and restored Germany’s position of restraining the Austro-Russian relations and its position as a mediator between the two countries. Austria-Hungary improved its relatively fragile position as a Great Power in Europe through the alliance, but at the cost of its foreign policy that was to some extent subject to Germany’s control. The Dual Alliance was in a dilemma at the very beginning. Both Germany and Austria-Hungary had the fears of “abandonment” and “entrapment”, and there were the risks of détente and conflict with hostile countries. In order to improve the internal relations of the alliance, the Austria-Hungary took advantage of Macedonian reforms to adopt a proactive foreign policy. In order to maintain the stability of the alliance, Germany repeatedly supported the policies that carried out by Austria-Hungary at critical moments in the process of Macedonian reforms to show its loyalty to the ally. The relationship between Germany and Austria. Hungary in the alliance gradually changed, which in turn pushed the Austria-Hungary to implement a more aggressive foreign policy. Գերմանա-ավստրիական դաշինքը Գերմանիայի ակտիվ դիվանագիտության կարևոր ձեռքբերումն էր, որը վերացրեց Ավստրո-Հունգարիայի՝ թշնամական երկրի վերածվելու ռիսկը։ Գերմանիան վերականգնեց ավստրո-ռուսական հարաբերությունների զսպումը և Ավստրիայի և Ռուսաստանի միջև միջնորդության կարգավիճակը։ Այս դաշինքի շնորհիվ Ավստրո-Հունգարիան բարելավեց իր դիրքերը որպես համեմատաբար փխրուն մեծ ուժ Եվրոպայում, սակայն Գերմանիայի հետ իր արտաքին քաղաքականության վրա որոշ սահմանափակումներ դնելու գնով: Գերմանա-ավստրիական դաշինքը հենց սկզբից գտնվում էր ծանր կացության մեջ: Գերմանիան եւ Ավստրիան անհանգստացած էին «մեկուսացված» լինելու հեռանկարի պատճառով։ Կար նաև թշնամական երկրների հետ մերձեցման և հակամարտության վտանգ։ Դաշինքի ներսում հարաբերությունները բարելավելու նպատակով Ավստրո-Հունգարիան օգտվում էր մակեդոնական բարեփոխումներից՝ ակտիվ արտաքին քաղաքականություն որդեգրելու համար: Դաշինքի կայունությունը պահպանելու համար Գերմանիան աջակցում էր Ավստրո-Հունգարիայի վարած քաղաքականությանը Մակեդոնիայի բարեփոխումների գործընթացում բազմաթիվ վճռորոշ պահերին՝ դաշնակիցների հանդեպ իր հավատարմությունը ցույց տալու համար։ Գերմանիայի եւ Ավստրիայի միջև դաշինքի առաջնային և երկրորդական հարաբերությունները աստիճանաբար փոխվեցին, ինչն էլ իր հերթին դրդեց Ավստրո-Հունգարիային ավելի ակտիվ և ինքնավստահ արտաքին քաղաքականություն վարել։
Keywords: History